Immunosuppressive Effects of Thallium Toxicity in Nile Tilapia Fingerlings: Elucidating the Rescue Role of Astragalus membranaceus Polysaccharides - Farag, Mayada R.; Alagawany, Mahmoud; Khalil, Samah R.; El-Hady, Eman W.; Elhady, Walaa M.; Ismail, Tamer Ahmed; Marini, Carlotta; Di Cerbo, Alessandro; Abdel-Latif, Hany M. R. (Frontiers in Veterinary Science, 2022)
This study evaluated the immunotoxic effects of thallium (Tl) in Oreochromis niloticus fingerlings and the recovery role of dietary Astragalus polysaccharides (AS). An 8-week experiment was designed where 180 fishes were randomly and equally assigned in triplicates into six groups: the control group (CNT) was reared in unpolluted water and fed a commercial diet, 2 groups were fed the commercial diet plus 0.15% and 0.30% AS (AS0.15 and AS0.30), respectively, the fourth group was exposed to a sublethal dose of Tl (41.9 μg L-1) (equal to 1/10 of 96-h LC50), and the last 2 groups were fed 0.15% and 0.3% AS, respectively, and concurrently exposed to Tl (41.9 μg L-1) (AS0.15+Tl and AS0.30+Tl). Fish hematobiochemical parameters, serum immunity (nitric oxide, total IgM levels, and lysozyme activity), transcription of hepatic interferon-gamma (IFN-γ), interleukin 1beta (IL-1β), and tumor necrosis factor-alpha (TNF-α), and resistance to Aeromonas hydrophila were assessed. Hematobiochemical parameters and serum immune indices were significantly decreased in the Tl-intoxicated group compared to the CNT group. Furthermore, Tl exposure significantly induced overexpression of IL-1β, TNF-α, and IFN-γ genes (4.22, 5.45, and 4.57-fold higher, respectively) compared to CNT values. Tl exposure also increased the cumulative mortality (%) in Nile tilapia challenged with A. hydrophila. Remarkably, groups fed AS0.15+Tl and AS0.30+Tl significantly ameliorated all aforementioned parameters but did not reach CNT values. Our findings suggest the possible immunomodulating roles of dietary AS in recovering the immunotoxic effects of Tl in Nile tilapia. We can conclude that dietary AS would be useful for maintaining the immunity of Nile tilapia fingerlings.